Efficacy of triphala extract and chlorhexidine mouth rinse against plaque accumulation and gingival inflammation among female undergraduates: A randomized controlled trial - Sahana Umesh Baratakke; Rekha Raju; Sushi Kadanakuppe; Nagashree R Savanur; Radha Gubbihal; Pallavi Swamy Kousalaya (Wolters Kluwer Medknow Publications, 2017)
Aim: To know the efficacy of Triphala extract and Chlorhexidine mouth rinse against plaque and gingival inflammation. Materials and Methods: A double blinded parallel arm randomised control trial was done among 60 participants aged 18-24 years. Participants were randomly allotted to three groups with 20 participants in each group of 0.6% triphala, 0.12% chlorhexidine and control group. Study was done in 2 phases of 21 days duration. During the experimental period, participants rinsed with the allocated mouth rinse 10ml twice daily for 30 seconds without any supervision. The plaque and gingival status were assessed using Silness and Loe and Loe and Silness at baseline and end of the phase. Statistical Analysis Used: The results were analysed using ANOVA(Analysis of Variance), Wilcoxon sign rank test and post hoc test with significant level at P value < 0.05. Results: Triphala and Chlorhexidine showed significant reduction in plaque and gingival scores as compared to Control group (P < 0.001). No significant difference was found between the plaque and gingival scores obtained with triphala extract and chlorhexidine mouth rinse. Conclusion: Triphala extract mouth rinse was effective in reducing plaque accumulation and gingival inflammation with reported no side effects.